2019
DOI: 10.1016/j.omtm.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Mediated Expression of AP-1-Neutralizing RNA Decoy Oligonucleotides Attenuates Transplant Vasculopathy in Mouse Aortic Allografts

Abstract: Transplant vasculopathy (TV), characterized by obstructive lesions in affected vessels, represents one of the long-term complications of cardiac transplantation. Activation of the transcription factor activator protein-1 (AP-1) is implicated in smooth muscle cell (SMC) phenotypic switch from contractile to synthetic function, increasing the migration and proliferation rate of these cells. We hypothesize that adeno-associated virus (AAV)-mediated delivery of an RNA hairpin AP-1 decoy oligonucleotide (dON) might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“… 7 This lab has a long-standing and ongoing tradition of using AAVs for potential therapeutic proposes. 8 , 9 , 10 The Marfan syndrome model chosen for the study is the fibrillin-1 hypomorphic mgR/mgR mouse, whose aortic aneurysm quickly evolves, usually ending in aortic dissection. Cultured Marfan aortic smooth muscle cells (SMCs) and aortic tissue showed a significant reduction in Regnase-1 protein levels.…”
Section: Main Textmentioning
confidence: 99%
“… 7 This lab has a long-standing and ongoing tradition of using AAVs for potential therapeutic proposes. 8 , 9 , 10 The Marfan syndrome model chosen for the study is the fibrillin-1 hypomorphic mgR/mgR mouse, whose aortic aneurysm quickly evolves, usually ending in aortic dissection. Cultured Marfan aortic smooth muscle cells (SMCs) and aortic tissue showed a significant reduction in Regnase-1 protein levels.…”
Section: Main Textmentioning
confidence: 99%
“…AP-1 is a transcription factor involved in the transcriptional regulation of genes implicated in cell proliferation and extracellular matrix production in response to inflammatory cytokines and oxidative stress [ 42 ].…”
Section: Effects Of Decoys On Non-atherosclerotic Cvdmentioning
confidence: 99%
“…Ex-plantation after 30 days and evaluation showed that AP-1 decoy oligonucleotide therapy reduced the intima-to-media ratio in the grafts by 41.5 percent. Additionally, in treated grafts, expression of cytokines and adhesion molecules were greatly decreased, as were MMP-9-positive cells, SMCs, and inflammatory cell infiltration [ 42 ].…”
Section: Effects Of Decoys On Non-atherosclerotic Cvdmentioning
confidence: 99%